Successful Management of Recurrent Pyothorax in a Cat: Clinical Findings with Medical and Surgical Approaches - Hyomi Jang; Seoyeon Kim; Yebeen Lee; Jongwon Park; Hyojun Kwon; Sunyoung Kim; Jiheui Sohn; Jong-in Kim; Dong-In Jung (Animals)
Feline pyothorax or thoracic empyema is a condition characterized by the accumulation of purulent exudate within the thoracic cavity due to infection [...]